Investigation of talent, talent management, its policies and its impact on working environment. Issue 3 (7th August 2017) - Saddozai, Sehrish Khan; Hui, Peng; Akram, Umair; Khan, Muhammad Saad; Memon, Suhail
Abstract : Purpose: The purpose of this paper is to explore broader and dynamic features of talent, talent management, its policies and its impact on academic working environment. Design/methodology/approach: This research was based on qualitative research in the form of unstructured interviews containing open-ended questions. Data were collected from the university management, deans, heads of departments (HoDs), assistant professors, associate professors and lecturers. The research was conducted in the form of interviews and the participants were asked to define talent, talent management (TM) policies, its usefulness and its impact on the working environment within the university. This study was conducted into two parts. In the first part, all deans, HoDs and human resource management (HRM) (stakeholders) were interviewed, and in the second part, all professors, associate professors, assistant professors and lecturers (talents) were interviewed. Findings: The present study investigated that talent and TM are very important in any academic organization. The impact of HRM on TM is very important, as it defines how an academic organization works to retain its talent and improve working conditions within the organization. In addition, this paper details the barriers that the human resource department faces with regard to TM and vice versa. Further, the authors attempted to ascertain the academic staff's perspectives, their needs and the difficulties they face within the university. Originality/value: This research paper shows the difficulties faced by the government institutions in China and Pakistan and how they cope with the current situation of TM within the available resources, polices and the impact of these on the working environment.